2023
DOI: 10.3390/w15020224
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Effect of Mining Dust Diffusion on Melting of the Adjacent Glacier: A Case Study in Xinjiang, China

Abstract: Given the typical disturbances in the aqueous environment in the alpine area because of mining activities in Northwest China, a case study highlighting the enhanced effect of mining dust diffusion on the melting of the adjacent glacier is presented here. Initially, a three-dimensional numerical model of the local airflow field was established by considering the effects of both mines and glaciers using the FLUENT software. Then, the diffusion path and size range of dust particles from the mines were simulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Zhang, Z.Y. [25] used Fluent software to simulate the diffusion path of dust particles in the mine and concluded that the local airflow field in the alpine zone is controlled by the "cold and hot double island effect" formed by the mine and the glacier. Xiu, Z.H.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, Z.Y. [25] used Fluent software to simulate the diffusion path of dust particles in the mine and concluded that the local airflow field in the alpine zone is controlled by the "cold and hot double island effect" formed by the mine and the glacier. Xiu, Z.H.…”
Section: Introductionmentioning
confidence: 99%